«I didn’t offer to shake hands; no one would shake hands with a Jew»: Escapism and the Ideological Stance in Naomi Novik’s Spinning Silver - Sara González Bernárdez (Universitat Autònoma de Barcelona, 2019)
Naomi Novik, an American writer of Lithuanian-Polish ascendency, is one of the most acclaimed voices in contemporary young-adult fantasy fiction. Her fantasies are heavily influenced by her cultural heritage, as well as by the fairy tale tradition, which becomes most obvious in her two standalone novels, Uprooted and the subject of this essay, Spinning Silver. As the quote chosen for this essay’s title demonstrates, Novik’s second standalone work constitutes one of the most obvious outward statements of an ideological stance as expressed within fantasy literature, as well as an example of what Jack Zipes (2006) called transfiguration: the rewriting and reworking of traditional tales in order to convey a different, more subversive message.